OPTIMIZATION TECHNOLOGY IN EFFORTS TO SUPPORT INCREASING WORK PRODUCTIVITY - Yuspan Zalukhu (SEAN Institute, 2021)
This research was conducted to determine the impact of technology on the work productivity of New Normal Café. The method used is a qualitative research method with a descriptive analysis approach. Based on the results of research technology is one of the important factors that can support the success of a company in achieving work productivity. By utilizing every available technology, the productivity of every New Normal Café workforce is increasing, so that New Normal Cafe can maintain company turnover during the covid-19 pandemic which only allows 50% of visitors from the cafe's total capacity. It can be concluded that to achieve work productivity, companies must optimize every existing technology, because every job and company operations are increasingly effective